Evaluation of a SOE Stack for Hydrogen and Syngas Production: a Performance and Durability Analysis1. Issue 4 (1st February 2017) - Kotisaari, M.; Thomann, O.; Montinaro, D.; Kiviaho, J.
Abstract: Solid oxide electrolyzer (SOE) are gaining growing interest in research because they can convert electricity into a chemical fuel with high efficiency. The present work investigates the performance of a 6‐cell SOE stack (80 cm 2 active area) in electrolysis and co‐electrolysis modes for producing hydrogen and synthetic fuel. Initially, the stack was operated and characterized in fuel cell mode at 750 °C. Operation was then changed to electrolysis mode. The stack performance was characterized with four different inlet gas compositions of various ratios of inlet steam and carbon dioxide at temperatures of 700, 750 and 800 °C. It was found that the stack performance depends primarily on the operation temperature and only to a small extent on the inlet gas composition. Finally, a steam electrolysis durability test of 1, 500 hours was performed at a current density of –0.775 A cm −2 (50% of reactant utilization) and at a temperature of 750 °C. The voltage trend showed that no degradation could be observed, which is a very promising result. In conclusion, the investigated stack appears suitable for syngas production. In the future, co‐electrolysis durability tests will be conducted to evaluate the effect of addition of carbon dioxide on the stack durability.